Analisis Sektor Pembiayaan dalam Mendorong Suatu Pertumbuhan Usaha Mikro, Kecil dan Menengah (UMKM) - Saputri, Isri Al Iqna; Riani, Devita; Syaharani, Maulitha Haliza; Hapsari, Pradipta Larasati Annisa Aulia; Nurailida, Nabila; Aisyah, Siti; Astawa, I Ketut (Peneliti.net, 2025)
MSMEs play a significant role in the national economy, but their growth is often hampered by various obstacles, especially in accessing financing from the formal sector such as banks and non-bank financial institutions. Some of the main obstacles faced by MSMEs in accessing financing include limited information, lack of financial literacy, strict requirements, and lack of collateral owned by business actors. The objectives to be achieved by the researcher in this study are to analyze the effect of access to the financing sector on the growth of micro, small and medium enterprises (MSMEs) and to describe the factors that hinder the accessibility of MSMEs. This study uses a qualitative and quantitative approach to evaluate the extent to which the financing sector can encourage the growth of MSMEs, as well as identify the hindering factors and solutions that can be applied to improve the accessibility of financing for MSMEs.